THE CHALLENGES IN IMPLEMENTING DIFFERENTIATED INSTRUCTION IN ENGLISH CLASSSES : A CASE STUDY IN AN EASTERN INDONESIA CONTEXT - Pendi Rosadi; Lestari, Yuni Budi; Hadi, Makmur (Ethical Lingua: Journal of Language Teaching and Literature, 2024)
The Merdeka Curriculum is the current Indonesian curriculum that suggests the implementation of Differentiated Instruction (DI) to cater to students with different learning styles, needs, and abilities. This study aims to identify and describe the teachers knowledge of the concept of Differentiated Instruction and the challenges of implementation DI in English Classes. This study used a descriptive qualitative research design. The data of the study were collected through in-depth interviews. The collected data were then analyzed using content analysis. This research was conducted in a government senior high school in West Nusa Tenggara, Indonesia. Three English teachers were purposively selected to be the participants of the study. From the results of the study, it was found that the teachers have a good understanding of the basic concept of direct instruction. The study also found several challenges facing the teachers in implementing DI which include the big class size, constraints with time and resources to design and deliver material for different learners. This study suggests that teachers play an active role as a facilitator for students in every learning process and are able to recognize the characters, learning interests of students, and learning styles of different students.